Usability strategies of instructional interface design courseware for inclusive education system - Tosho, Abdulrauf (2015)
Research in aiding learners with instructional design has been one of the focuses in the area of user interface design. However, studies have revealed that 80% of learning materials such as textbook and courseware are rigidly designed, besides studies on usability strategies for courseware design in Inclusive Learning is very limited. Accordingly, the instructional approach in courseware needs to be designed based on an appropriate conceptual design model to ensure that it meets the needs of learners. However, many existing design models of courseware have not provided a set of proper specific requirements and enough usability strategies for instructional interface in order to encourage the learners in utilizing the courseware. Hence, this study proposes Instructional Interface Design for Courseware (IID4C) model that caters the needs of diverse learners. The objective is to ensure that the design of courseware meets the needs of inclusive learners through instructional interface in terms of structure, layout, and navigation. Iterative Triangulation Method has been utilized in conducting the research. This includes comparative analysis, expert review, prototyping, and user experience testing. Findings of user experience testing indicate that the IID4C model is able to fulfill the learners instructional interface needs. This study shows that the IID4C model is useful for information accessibility and contributes for the designing and developing instructional courseware.